Climate change in the Arctic: Testing the poleward expansion of ticks and tick‐borne diseases. Issue 7 (1st February 2023) - McCoy, Karen D.; Toty, Céline; Dupraz, Marlène; Tornos, Jérémy; Gamble, Amandine; Garnier, Romain; Descamps, Sébastien; Boulinier, Thierry
Abstract: Climate change is most strongly felt in the polar regions of the world, with significant impacts on the species that live there. The arrival of parasites and pathogens from more temperate areas may become a significant problem for these populations, but current observations of parasite presence often lack a historical reference of prior absence. Observations in the high Arctic of the seabird tick Ixodes uriae suggested that this species expanded poleward in the last two decades in relation to climate change. As this tick can have a direct impact on the breeding success of its seabird hosts and vectors several pathogens, including Lyme disease spirochaetes, understanding its invasion dynamics is essential for predicting its impact on polar seabird populations. Here, we use population genetic data and host serology to test the hypothesis that I. uriae recently expanded into Svalbard. Both black‐legged kittiwakes ( Rissa tridactyla ) and thick‐billed murres ( Uria lomvia ) were sampled for ticks and blood in Kongsfjorden, Spitsbergen. Ticks were genotyped using microsatellite markers and population genetic analyses were performed using data from 14 reference populations from across the tick's northern distribution. In contrast to predictions, the Spitsbergen population showed high genetic diversity and significant differentiation from reference populations, suggesting long‐term isolation. Host serology also demonstrated a high exposure rate to Lyme disease spirochaetes (Bbsl). Targeted PCR and sequencing confirmed the presence of Borrelia garinii in a Spitsbergen tick, demonstrating the presence of Lyme disease bacteria in the high Arctic for the first time. Taken together, results contradict the notion that I. uriae has recently expanded into the high Arctic. Rather, this tick has likely been present for some time, maintaining relatively high population sizes and an endemic transmission cycle of Bbsl. Close future observations of population infestation/infection rates will now be necessary to relate epidemiological changes to ongoing climate modifications. Abstract : We examine whether recent observations of Ixodes uriae ticks infesting breeding seabirds in the high Arctic represent a recent poleward expansion of the parasite due to climate change. Surprisingly, genetic data suggest that these ticks have been present in the region for some time, maintaining high local diversity despite the harsh environmental conditions, and vectoring infectious agents among breeding birds. Indeed, we demonstrate the presence of the Lyme disease spirochaete Borrelia garinii in ticks of the high Arctic for the first time.